INVESTIGATION OF WATER BLOOM IN KAMYANSKE RESERVOIR USING GIS AND REMOTE SENSING METHODS - GLUHOTA, Vitaly; SHEVCHUK, Serhii (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2023)
The issue of studying the phenomenon of eutrophication and its emergence, which is an urgent problem for the provision of water in our country, has been investigated. It has been established that active water use, the construction of industrial and social infrastructure objects at water intakes, and the discharge of a large amount of wastewater into rivers, lakes, and reservoirs exceed the self-purification capacity of aquatic ecosystems and lead to their resource degradation. It is noted that a manifestation of such water body degradation is the phenomenon of water bloom, which intensifies the eutrophication process, disrupting or completely stopping self-regulation and self-purification processes, deteriorating the overall system, potentially leading to the formation of toxic algae, water pollution, and posing a threat to the inhabitants of water bodies and human health. An analysis of the concept of eutrophication has been conducted, noting that it is a natural process of "feeding" water bodies. The causes of excessive eutrophication have been analyzed, including its natural and anthropogenic factors. The features of GIS and RS methods for monitoring, studying, and forecasting the phenomenon of water bloom have been characterized. The hydrochemical and hydrographic parameters of the Kamianske Reservoir, the smallest in the Dnieper cascade of reservoirs but with a characteristic manifestation of water bloom, have been determined. Using Landsat-8 and Sentinel-2 satellite data, the peculiarities of water bloom in the Kamianske Reservoir for 2021 have been shown. A correlation has been established between the water temperature in the reservoir and its blooming, revealing that the warming of the Kamianske Reservoir's water is the cause of its excessive blooming. The consequences of water bloom for the Kamianske Reservoir have been investigated using GIS and RS methods, including the determination of the areas of water body overgrowth. The main geoecological approaches to solving the water bloom issue for the Kamianske Reservoir have been substantiated.
Keywords: eutrophication; water bloom; Kamyanske reservoir; Landsat-8; Sentinel-2; normalized difference vegetation index (NDVI); normalized difference turbidity index (NDTI); normalized relative algal index (NDAI); EO Browser; QGI